Johannes Heldéns Astroekologi: Et mesh af konstellationer og mellemrum - Mose, Gitte (Tidskrift för litteraturvetenskap, 2020)
Johannes Heldéns Astroecology. A Mesh of Constellations and Gaps The article presents a discussion of this on going multimodal and multimedial work seen in relation to Timothy Morton’s ecological thinking. The artist’s outspoken interest in exploring what might happen between the combinations of the different modalities of his works is discussed within a frame of so-called ”liminal spaces”.